Preparation of Isoflavone glucosides from Soy germ and β-Glucosidase from Bacillus coagulans PR03 for Isoflavone aglycones Production - Supakit Chaipoot (2020)
© 2019, Chiang Mai University. This research optimized isoflavone aglycones production from soy germ. The processes included isoflavone glucosides extraction from soy germ to use as a precursor for isoflavone aglycones production. β-glucosidase was produced from B. coagulans PR03 and used to convert glucosides form to aglycones. For the β-glucosidase production using Plackett and Burman Design (n=8) and 22 factorial experiment with central composite design, the suitable medium containing peptone (2.00%), beef extract (14.84%), glucose (2.00%) and magnesium sulphate (0.10%) with pH 7.96 was used and incubated at 30 °C. The resulting β-glucosidase activity was 4.01 mU/ml. However, the isoflavone glucosides was extracted by use of soy germ in 80% ethanol at a ratio of 1:5 with high power ultrasonication technique at 80 oC for 160 min using a completely randomized design. The extracted isoflavone glucosides contained daidzin, genistin and glycitin of 307.47, 214.84 and 73.63 mg/100 g. (dry basis), respectively. Finally, isoflavone aglycones production was optimized using 22 factorial experiment with central composite design, the total isoflavone glucosides (595.95 mg/100 g. dry basis) was convert to isoflavone aglycones (112.90 μg/ml) by β-glucosidase at 37.5 °C for 120 hours.